Uma proposta de realização de uma feira científica de física em uma escola de ensino médio - Zandomênico, João Maurício (2014)
This studyexamined a proposal forexecuteaPhysicsScienceFairin ahighschool inthe State in the State ofEspírito Santo. TheScience Faircanbe configured as anon-formaleducation activity, which in this casewas conducted aspart of the activitiesof formal education, as the results of the evaluationwere used in thepaymentof the pointsof the semester. 152studentsof 2nd and 3rdyear of high school, divided into29groups4-6students, who developedthe experimentsand wereinvolvedpresentationmadeduring the Fair, under the supervision of the teacher/student masteringresponsibility. The whole projectlastedthree months, thisplanninguntilthe day of theScientificFair. Tofacilitate theproject evaluationand data collectionfor the work ofmasters, opinion questionnairesof studentsapplied before andafter theFair, monitoring reportsof student work, protocolsfor evaluationof foreignteachersatschool,conceptualissueswere developedpresentedsomeexperimentsandexternal evaluatorsinterviewquestionnaire.Data were compiledusingdescriptive statisticaltools. The resultsindicate thatthis eventconstitutesastrategy formotivatingstudents, as were persistentand interested in thedevelopment of tasks. Showed evidenceof the difficultyof studentsin the process ofdidactic transpositiontothe presentationof the experiments, which is indicativeof alow level ofabsorption ofconceptsfrom visitors. The opinions ofstudentson the completionof the Fair, as well as the benefits forteaching practiceinview of theteacher/student masteringwere also observed. The workwas highlypositivewith respectto the involvement ofstudentsin the tasks ofScientificFairrevealedandpoints that need tobe betterstructuredto achieve abetter jobin presentingexperimentsfor visitors.